Motor learning in golf—a systematic review - Barzyk, Philipp; Gruber, Markus (Frontiers in Sports and Active Living, 2024)
Golf is a sport that consists of complex movement skills that need to be executed with utmost precision. Consequently, motor skill learning plays a crucial role in golf, and large numbers of studies address various methods of motor learning. In the present review, we give a systematic overview of randomized controlled trials (RCTs) on motor learning of golf-specific motor skills. Three electronic databases were searched for RCTs looking at the effect of at least one learning method on performance in a golf-specific motor task. We grouped the studies depending on the learning strategies “cognitive training”, “practice scheduling”, “augmented feedback”, “implicit and explicit learning” and “focus of attention”. Fifty-two RCTs met the eligibility criteria and were included in the systematic review. Superior methods within their respective strategies were an external focus of attention and increasing contextual interference, as well as errorless learning. For “cognitive training” and “augmented feedback”, no single method can be considered the most favorable. The overall biggest limitations were the lack of statistical power for more than half of the RCTs, and the fact that most studies of the present review investigated simple putting tasks in novices only. Although we have shown superiority of specific learning methods, transferability of the recommendations that can be derived from simple golf tasks in novices to sport-specific tasks in advanced players still has to be demonstrated and require study designs with the intention to provide practical recommendations for coaches and athletes in the sport of golf.